KIR downregulation by IL-12/15/18 unleashes human NK cells from KIR/HLA-I inhibition and enhances killing of tumor cells - Ewen, Eva-Maria; Pahl, Jens; Cerwenka, Adelheid (European journal of immunology, 2018)
To exploit autologous NK cells for cancer immunotherapy, it is highly relevant to circumvent killer cell immunoglobulin-like receptor (KIR)-mediated self-inhibition of human NK cells by HLA-I-expressing tumor cells. Here, we show that stimulation of NK cells with IL-12/15/18 for two days led to downregulation of surface expression of the inhibitory KIR2DL2/L3, KIR2DL1 and KIR3DL1 receptors on peripheral blood NK cells. Downregulation of KIR expression was attributed to decreased KIR mRNA levels which could be re-induced already 3 days after re-culture in IL-2. Reduced KIR2DL2/L3 expression on IL-12/15/18-activated NK cells resulted in less inhibition upon antibody-mediated KIR engagement and increased CD16-dependent cytotoxicity in redirected lysis assays. Most importantly, downregulated KIR2DL2/L3 expression enabled enhanced cytotoxicity of IL-12/15/18-stimulated NK cells against tumor cells expressing cognate HLA-I molecules. NK cells pre-activated with IL-12/15/18 were previously shown to exert potent anti-tumor activity and memory-like long-lived functionality, mediating remission in a subset of acute myeloid leukemia (AML) patients in a clinical trial. Our study reveals a novel mechanism of IL-12/15/18 in improving the cytotoxicity of NK cells by reducing their sensitivity to inhibition by self-HLA-I due to decreased KIR expression, highlighting the potency of IL-12/15/18-activated NK cells for anti-tumor immunotherapy protocols.